Environmental and Health Costs of Europe's Shift from Gas to Coal Amidst the Energy Crisis - Mario Liebensteiner; Alex Mburu Kimani (CESifo GmbH, 2025)
The gas price explosion during the 2021/22 European energy crisis prompted a shift from gas- to coal-fired electricity production. Empirical evidence on the environmental and health consequences of such a fuel-price shock - as opposed to policy reforms - is scarce. We fill this gap by quantifying how exogenous gas price surges reorder coal-gas marginal costs and, in turn, affect emissions and health outcomes. Using daily data (2015-2023) for six EU countries with substantial gas-to-coal switching potential, we estimate a two-stage residual inclusion (2SRI) model to obtain causal effects of days on which gas is more expensive than coal. During the 510 days of the 2021/22 gas price surge when coal was cheaper, coal-fired generation rose by 23% (53 TWh, 95% CI: 43-63), driving a 10% increase in CO2 (36 Mt, 95% CI: 28-45 Mt), 19% in PM2.5 (187 t, 95% CI: 152-222 t), 10% in NOx (8,442 t, 95% CI: 6,573-10,715 t), and 24% in SO2 (16,238 t, 95% CI: 10,947-21,658 t). Applying literature-based damage factors, we find indicative increases in premature deaths and serious illnesses, with additional external health costs exceeding one billion EUR(2021). All figures are computed relative to a model-based counterfactual in which gas remained the cheaper option and represent short-term effect that disregard longer-term structural adjustments. The results highlight the substantial welfare costs of fuel price shock-induced switching and inform the design of policies that internalize these externalities.
Keywords: I15; Q41; Q53; 330; air pollution; CO2 emissions; energy crisis; gas price shock; gas-to-coal switch; health effects